Developing an aggregate metric to measure and benchmarking energy performance - JEMMAD, Kamal; HMIDAT, Abdelhamid; SAAD, Abdallah (International Journal of Sustainable Energy Planning and Management, 2019)
As key elements of energy planning, ISO 50001 recommended inter alia identifying appropriate indicators to monitor and measure energy performance. Benchmarking can be a helpful tool to establish energy efficiency or performance indicators. While we agree that is hard to get an absolutely universal indicator aggregating several physical indicators defined in differing units; it is however possible to expand the area of cases covered or improve its characteristics such as accuracy, representativeness and simplicity. In this paper, we developed an aggregated dimensionless “Indicator for Energy Benchmarking” (IEB) to enhance the range of models of indicators dedicated to the engineering field. The systems targeted are low and middle level systems of the energy indicators pyramid. We built the proposed indicator based on specific characteristics: process decomposition-oriented, increasing when energy consumption decreases, dimensionless, with limited threshold value to 1. Consequently, the indicator provides many advantages in comparison to simple metrics and complex indicators such as: direct detection of energy use failure processes, creating interdependence between benchmarked systems scores, no need for data history to start benchmarking of a multisystem. IEB can be implemented as an integral part of many energy management or energy efficiency standards, methodologies or tools such as EN 16231:2012 and ISO 50001:2018. In last section, we calculate the indicator for 2 central sterile service departments of 2 university hospitals in Morocco to show its potential and operating mode.